JUMPA Vol.2 No.1 Feb 2015 ANALISIS PRODUK, JASA, DAN KUALITAS PELAYANAN DALAM MEMENGARUHI KEPUASAN NASABAH: ANALISIS PRODUK, JASA, DAN KUALITAS PELAYANAN DALAM MEMENGARUHI KEPUASAN NASABAH - Novita Sari Sekolah Tinggi Ilmu Ekonomi Y.A.I. Jakarta; Alfan Lumbardo Sekolah Tinggi Ilmu Ekonomi Y.A.I. Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
This study aimed to determine the effect of Products, Services and Islamic Banking Service Quality on Customer Satisfaction simultaneously Syariah Mandiri Bank Jakarta. This study uses associative causal research. The sample used in the study was 112 respondents from Customers Bank Syariah Mandiri in Jakarta. In this study the authors used SPSS version 19 o'clock as a tool to test the normality of data, the classical assumption test, descriptive statistics, t test analysis and test F and test the coefficient of determination with a significance level of 5% (0.05. Which is an indicator of independently variable in this study is a Product, Service and Service Quality Bank Syariah while a dependent variable is Customer Satisfaction Bank Syariah Mandiri in Jakarta. The results of the t test performed on variables Products and Services Bank Syariah Mandiri showed an influence on Customer Satisfaction of Bank Syariah Mandiri in Jakarta where the obtained value of t > t table as well as the value of each probability signifikanya showed less than (<0,05). As for the variable quality of service has not indicated an influence on Customer Satisfaction with Bank Syariah Mandiri Jakarta obtained where the value of to >t table and signifikanya probability value indicates less than (< 0,05).For double regression (F test) Products, Services and Islamic Banking Service Quality on Customer Satisfaction simultaneously Syariah Mandiri Bank Jakarta test statistic obtained Fo> F test) and probability of significance (<0,05).